Geotechnical aspects of pavements : reference manual / participant workbook - Christopher, Barry R. 1949- (U.S. Dept. of Transportation, Federal Highway Administration : National Highway Institute, 2006)
This 2006 manual covers the latest methods andprocedures to address the geotechnical issues in pavement design, construction andperformance for new construction, reconstruction, and rehabilitation projects.
Cover title.
"May 2006."
Loose-leaf format.
"Publication no. FHWA NHI-05-037."
Keywords: Pavements -- Design and construction -- Handbooks, manuals, etc.; Pavements -- Subgrades -- Handbooks, manuals, etc.; Roads -- Base courses -- Handbooks, manuals, etc.; Road drainage -- Handbooks, manuals, etc.; elektronické knihy; electronic books